Preliminary Study on the Best Working Posture for Motorcycling - Muhammad Izzat Nor, Ma'arof; Abdul Rahman, Omar; Zamalia, Mahmud; Nasir, Senin (Human Factors and Ergonomics Society Malaysia, 2016)
Motorcycle riding posture has generally been documented to be ergonomically unfitting for human. This is because the human operator is mostly seated at static with minimal sitting support and without a backrest. Thus, it is emphasized that there is a link between motorcycling riding posture (motorcycle ergonomics) with motorcycle road accidents. The objective of this study was to identify the best riding posture for motorcycling based on a survey study. The significance of this study was to investigate the public perception on the best motorcycling riding posture. A survey research with 30 healthy motorcyclists (between the ages of 18 – 25 years old) from diverse backgrounds via questionnaire was conducted. The data was analyzed via the Statistical Package Service and Solution (SPSS) with the statistic for level of confidence at 95% (1.96), expected proportion (in proportion of one) at 0.5 and the precision (in proportion of one) at 0.1 (due to the limitation of resources). For greater grasp of understanding in regards to the results obtained, veteran motorcyclists (above 14 years of riding experience) were also consulted. The results summarized that the best riding posture for motorcycling is the upright riding posture. From the consultation, it was detailed that the particular riding posture was most probably selected due to the following reasons: i) being the most versatile/flexible riding posture, ii) capable of providing an acceptable level of motorcycling comfort, iii) propose minimal level of physical hazard. Even so, the results also highlighted by the consultants that other factors such as modes of travelling and riding styles would also influence in determining the best riding posture. Conclusively, based on the survey, the upright riding posture is the best riding posture. Nevertheless, the result is only limited to physical and psychological (perceptions) evaluations without examining the riding postures from the physiological perspective such as via the use of sEMG measurement.